Social and Structural Determinants of HIV Treatment and Care Among Hispanic Women and Latinas Living with HIV Infection in the United States: A Qualitative Review: 2008?2018 - Angelica Geter Fugerson; Madeline Y. Sutton; Donna Hubbard McCree (Mary Ann Liebert, 2019)
Purpose: In 2017, among all women in the United States, Hispanic women and Latinas (Hispanics/Latinas) accounted for 16% of women with HIV. Populations with high HIV disparities, including Hispanics/Latinas, experience treatment and care outcomes that are well below the national goals. The objective of this qualitative review was to identify social and structural barriers to HIV care from the perspective of Hispanics/Latinas. Methods: Our qualitative review was conducted in six stages: (1) searched and reviewed studies with a focus on Hispanics/Latinas with diagnosed HIV in the United States, published between January 2008 and August 2018; (2) removed unpublished reports and dissertations; (3) limited the search to keywords linked to social and structural HIV outcomes; (4) limited our search to studies that included samples of ?30% Hispanics/Latinos and ?30% female; (5) extracted and summarized the data; and (6) conducted a contextual review to identify common themes. Results: We identified 1796 articles; 84 titles and abstracts were screened for full-text review; 16 were selected for full review; and 6 articles met our inclusion criteria for final analysis. Barrier themes to HIV care for Hispanics/Latinas included HIV-related stigma from health professionals, legal consequences of seeking HIV services (including fear of deportation), and language barriers while utilizing HIV services and medications. Conclusion: Although the evidence addressing facilitators and barriers to care among HIV-positive women is sparse, interventions, resources, and enhanced training for health professionals to decrease social and structural barriers to HIV services for Hispanics/Latinas are warranted.